(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: The hotel and restaurant industries wield a pivotal influence on the global economy, but they are exquisitely vulnerable to economic oscillations. Comprehending the economic reverberations on these sectors is paramount for formulating efficacious strategies to surmount obstacles and perpetuate growth. Objective: This paper scrutinizes the economic repercussions on the hotel and restaurant industries and probes the factors that sway their performance amidst economic recessions. It also investigates the organizational practices and stratagems implemented to grapple with recessions and ensure survival. Methodology: Cross sectional field survey was executed in Delhi, India, with data amassed from 10 five-star hotels and 30 quick-service restaurants employing a questionnaire. Respondents were in age bracket of 31-50 years in which 70% were male and 30% of the respondents were manager. Chi-square tests, mean calculations, standard deviation calculations, and t-tests were deployed for data analysis. Result: The results unveil momentous associations between factors such as recession causes, severity of impact, measures adopted to combat the recession, and strategies embraced subsequent to the recession. Additionally, the study examines expectations regarding recovery time and organizational practices for retaining employees during a recession. Conclusion: The findings yield invaluable insights into the industry’s response to economic recessions and proffer guidance for hotel and restaurant proprietors, managers, and staff to augment their competitiveness and navigate arduous economic circumstances.